Design and standardization of a test of spatial awareness and distance for the skills of passing from above and below for volleyball players aged (12-14 years) - Mohammed, Khalil (Journal of Physical Education, 2024)
The research aims: Designing a test of spatial awareness and distance for the skills of passing from above and below for volleyball players aged (12-14 years) and extracting standard scores and levels. The descriptive survey method was adopted. The research sample consisted of players from specialized schools for sports talent in volleyball, numbering (120) players in (6) specialized schools (Baghdad, Diwaniyah, Anbar, Samawah, Babylon, Kirkuk), as the researcher chose the players. Males aged (12-14 years). After that, the researcher divided the selected sample into a survey consisting of (10) players. To build the test, (50) players were selected, and the scientific foundations were found, and (60) players were chosen to codify the test and extract grades and standard levels. After that, the researcher designed a test. Spatial perception and distance for the skills of passing from above and below, out of his belief in evaluating the level of skill of the player at the level of the two skills. The scientific foundations of honesty, consistency, and objectivity were extracted, as well as the standards and levels that led to conclusions and recommendations, the most important of which are: A test was reached that takes into account distance and location for volleyball players. At the ages of 12-14 years, the largest percentage of results appeared within the Very Good level, which indicates that the sample’s level of perception was positive towards the test. The necessity of researching and investigating variables, whether physical, motor, or mental, that work to improve skill performance. It is necessary to use the test on an ongoing basis for the purpose of evaluating the player and identifying his level, as well as evaluating training programs.